2016
DOI: 10.1289/ehp.1408981
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Ambient Air Pollution, Placental Mitochondrial DNA Content, and Birth Weight in the INMA (Spain) and ENVIR ON AGE (Belgium) Birth Cohorts

Abstract: Background:Mitochondria are sensitive to environmental toxicants due to their lack of repair capacity. Changes in mitochondrial DNA (mtDNA) content may represent a biologically relevant intermediate outcome in mechanisms linking air pollution and fetal growth restriction.Objective:We investigated whether placental mtDNA content is a possible mediator of the association between prenatal nitrogen dioxide (NO2) exposure and birth weight.Methods:We used data from two independent European cohorts: INMA (n = 376; Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 39 publications
6
86
3
2
Order By: Relevance
“…Nonetheless, from the stance of health effects in the Madrid, it is PM 2.5 concentrations that show the most impact on the population, children and persons over the age of 75 years [5153]. The fact that PM 2.5 is the environmental chemical pollutant which displays a statistically significant association with the three indicators of low weight analysed in this study is not in contradiction with other studies in which NO 2 has been associated with adverse birth variables [6,11,12]. Furthermore, as in the case of NO 2 , there are many papers that link PM 2.5 to adverse birth variables [10,22,24].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Nonetheless, from the stance of health effects in the Madrid, it is PM 2.5 concentrations that show the most impact on the population, children and persons over the age of 75 years [5153]. The fact that PM 2.5 is the environmental chemical pollutant which displays a statistically significant association with the three indicators of low weight analysed in this study is not in contradiction with other studies in which NO 2 has been associated with adverse birth variables [6,11,12]. Furthermore, as in the case of NO 2 , there are many papers that link PM 2.5 to adverse birth variables [10,22,24].…”
Section: Discussioncontrasting
confidence: 66%
“…In recent years, various studies have linked exposure during pregnancy to chemical environmental pollutants present in the urban atmosphere to a number of adverse birth outcomes [14], including low birth weight (LBW) [5,6]. LBW, defined as any newborn having a weight of less than 2,500g [7], can give rise to lifelong impairments due to respiratory, circulatory and neurological diseases and disorders [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…36-38 In a pooled analysis from two European birth cohorts, Clemente et al reported decreased placental mtDNA abundance with in utero exposures to NO 2 . 36 Two separate studies from the ENVIR ON AGE cohort also showed elevated mitochondrial 8-hydroxy-2′-deoxyguanosine levels associated with decreased mtDNA abundance in both maternal and newborns blood in response to prenatal PM 10 exposures. 37,38 Moreover, studies of the environmental influence of mitochondria have been extended to DNA methylation machinery, where Byun et al .…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Prenatal exposure to NO 2 —a gaseous precursor of NO 3 - has also been associated with decreased placental mtDNA abundance. 36 In one of the recent publications, Shi et al reported a positive association between exposure to PM 2.5 -containing NO 3 - and exhaled nitric oxide—a well-known biomarker for respiratory inflammation. 44 Nevertheless, we have not been able to identify experimental studies that describe the toxicologic effects of nitrate-rich particles.…”
Section: Discussionmentioning
confidence: 99%
“…6063 More recently, placental mitochondrial DNA content, which can be diminished by oxidative stress, has been shown to be lower in the settings of both higher exposure to air pollution and lower birth weights. 64 While biologically plausible, definitively determining whether environmental factors cause adverse birth outcomes is difficult. Randomized trials of exposure, the gold standard to determine causal relationships, are unethical when an exposure is known to be harmful.…”
Section: Environmental Exposuresmentioning
confidence: 99%